Calcium Deficiency Effects in Leucaena leucocephala Lam. De Wit. Seedlings Suitable for Afforestation in Degraded Lands of Uttar Pradesh - Mishra, Kalpana (Indian Forester, 2001)
Leucaena leucocephala Lam. de Wit. is a suitable plant for afforestation in degraded lands of Uttar Pradesh, India. But so for, no attention has been paid to study their nutritional requirement and growth. For the first time disorders of calcium deficiency have been observed in this plant at seedling stage by growing them in low (0.08 gl-1) calcium. As compared to the plants at adequate (8.0 gl-1) calcium the growth of low calcium plants were reduced. Calcium deficiency in Leucaena spp. not only depressed the girth of the stem and branches but markedly reduced the calcium concentration in all parts of the plant. The decrease in calcium was most marked in roots than other parts of the deficient plants. Dye back syndrome was more prominent at later stages of growth.